Pengaruh Pajak Daerah, Retribusi Daerah, Dana Alokasi Umum dan Dana Alokasi Khusus Terhadap Alokasi Belanja Modal - Muhammad Farhan Muchtar; Dirvi Surya Abbas; Sigit Budi Santoso (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
This research aims to determine the effect of regional taxes, regional levies, general allocation funds, special allocation funds on capital expenditure allocation (survey in the city/district of Bengkulu province for the 2014-2018 period). The research time period used was 5 years, namely the 2014-2018 period. The population of this study covers all cities and districts of Bengkulu province in the 2014-2018 period. The sampling technique uses purposive sampling technique. Based on predetermined criteria, 10 cities/districts were obtained. The type of data used is secondary data obtained from the official website of the Central Statistics Agency (BPS) and the Directorate General of Financial Balance (www.djpk.kemenkeu.go.id). The analytical method used is panel data regression analysis using Eviews software version 9.0. The panel data regression model used is the Common Effect Model. In this research the dependent variable is capital expenditure and the independent variables are local taxes, general allocation funds and special allocation funds. The research results show that regional levies have an influence on capital expenditure, while regional taxes, general allocation funds, special allocation funds do not have a significant influence on capital expenditure.